Biosynthesis of silver nanoparticle from water extract and decaffeinated extract from green tea - نجلاء محمد وريث; عائشة محمد القلال; سليمة أنور دمونة (African Journal of Advanced Pure and Applied Sciences, 2025)
Biosynthesis of metallic nanoparticles has attracted tremendous attention in recent years, numerous environmentally synthesis methods have been developed yielding nanoparticles via low cost, eco-friendly, and simple approaches. In this study, silver nanoparticles were synthesized using ultrasonic wave, Green Tea extract at room temperature, silver nanoparticle successfully synthesized. The formation of silver nanoparticle is confirmed by UV-VIS spectroscopy the absorption beak of surface plasmon resonance for nanoparticle synthesis from Green Tea extract at 444 nm while the nanoparticle synthesis from decaffeinated extract at 436nm. The FT-IR results revealed that the functional chemical groups in Green Tea significantly contributed to the synthesis of nanoparticles. The caffeine removal from Green Tea causes shifted in the peak of surface plasmon resonance to lower wavelength and the nanoparticles take more time to form.